Preschoolers’ temperament and social functioning in novel and routine contexts - Vaughan, Helena Shoplik; Teglasi, Hedwig (Frontiers in Psychology, 2022)
The centrality of social competence to children’s short and long-term well-being has sparked interest in the factors that contribute to its development, including temperament, a set of biologically based dispositions. A large body of work documents two types of temperamental dispositions associated with young children’s social functioning: reactivity and regulation. There is consensus about the detrimental effects of negative reactive tendencies, called negative affective reactivity (NA), and about the beneficial effects of regulatory tendencies, called effortful control (EC), on social functioning. Although NA is exacerbated in unfamiliar contexts, the role of contexts in its relation to social functioning has not been systematically addressed. To investigate the contribution of NA and EC to social functioning in Novel and Routine conditions, we devised a structured interview of adaptive responsiveness (AR), which was completed by parents of preschoolers along with a comprehensive temperament questionnaire. Children completed an individually administered task measuring emotion-situation knowledge (N=92) and their teachers completed a standard social competence questionnaire. To test this study’s primary hypothesis, we conducted a path analysis that controlled for variance shared across contexts and temperamental traits. NA emerged as the only unique predictor of social functioning, in the Novel context and EC emerged as the only unique predictor of social functioning, in the Routine contexts. Bivariate analyses, conducted without controls, showed all reactive traits to correlate exclusively with AR in the Novel contexts, but regulatory traits showed a mixed pattern, one correlating with AR in both contexts and one correlating with AR in the Novel context.